2021
DOI: 10.1016/j.parkreldis.2021.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical perception and management of Parkinson's disease during the COVID-19 pandemic: A Canadian experience

Abstract: Background The COVID-19 pandemic has necessitated the social isolation of the population and the rapid implementation of remote care for patients with neurodegenerative diseases. The objective of this study was to explore the perceived impact of confinement in patients with Parkinson’s disease and document the effects of gender and living environment. Methods We recruited two cohorts from the Canadian provinces of Québec and Alberta, which differed in the dynamics of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…However, our data indicate that although technical options were accessible in most PwP (even those with p-LTC, who additionally might not only need technical options but also care staff support to use the technology), acceptance and use of this technique was rather low in both groups. Although telemedicine approaches have been shown to be effective [ 60 , 61 ] and are widely recommended for PwP [ 16 , 32 , 62 ], even by the International Parkinson and Movement Disorder Society [ 1 ], our findings are congruent with previous studies documenting that even high levels of satisfaction with telemedicine did not translate into a sustained interest or use of this health care approach [ 2 , 12 ]. Extensive promotion of remote or virtual care modes that have been found to be as effective as in-person communication [ 63 ] or alternative offerings (e.g., conducting more house calls by medical and/or therapeutical staff, cross-sectoral approaches with PD nurse specialists as in other countries that are only rarely deployed in Germany so far [ 64 ]) should be focused on in the future.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, our data indicate that although technical options were accessible in most PwP (even those with p-LTC, who additionally might not only need technical options but also care staff support to use the technology), acceptance and use of this technique was rather low in both groups. Although telemedicine approaches have been shown to be effective [ 60 , 61 ] and are widely recommended for PwP [ 16 , 32 , 62 ], even by the International Parkinson and Movement Disorder Society [ 1 ], our findings are congruent with previous studies documenting that even high levels of satisfaction with telemedicine did not translate into a sustained interest or use of this health care approach [ 2 , 12 ]. Extensive promotion of remote or virtual care modes that have been found to be as effective as in-person communication [ 63 ] or alternative offerings (e.g., conducting more house calls by medical and/or therapeutical staff, cross-sectoral approaches with PD nurse specialists as in other countries that are only rarely deployed in Germany so far [ 64 ]) should be focused on in the future.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to these suggestions and the general limitations, disruptions of everyday activities and reduced access to health care and therapists might further complicate the situation of people with Parkinson’s disease (PwP) during the COVID-19 pandemic. Global and regional studies from America (US, Canada, Brazil), Asia (China, Japan, South Korea, India, Iran Israel, Turkey), North Africa (Egypt), or European countries (Luxembourg, Netherlands, UK, Italy, Spain, Slovenia) reported wide-ranging consequences of the pandemic on PwP, such as worsened motor and non-motor symptoms [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], a negative impact on mental health [ 29 ], a decline in quality of life [ 20 , 21 , 30 ], disrupted social and medical activities [ 12 , 13 ], impaired access to PD medication [ 21 , 31 , 32 ], or other unmet needs such as emotional distress, problems with rescheduling appointments with health care providers, and reduction in physical activity [ 2 , 14 , 20 , 22 , 24 , 33 , 34 ]. On the other side, although hours of caregiving at home and caregiver burden increased [ 33 ], patients and caregivers seem to be well informed and to have coped well in some studies [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rural communities often have limited access to technology and technological support. Other studies have found that PWP living alone, female individuals, those with lower income, and with cognitive impairment or psychiatric symptoms were disproportionately affected by the pandemic [21,[59][60][61].…”
Section: Disparities In Parkinson Disease Carementioning
confidence: 97%
“…Moreover, in a multicenter, international case series of 27 PwP, 22% has developed sleep disturbances as part of the long-COVID syndrome, suggesting that long-term sleep-related sequelae might also be expected ( Leta et al, 2021 ). An online questionnaire of 417 PwP in Canada, assessing the physical and mental wellbeing, the daily activities and their PD symptoms, has revealed an aggravation of sleep disorders among those residing in Quebec, but not in other areas, leading the authors to suggest that some subpopulations might be more sensitive to social isolation and changes in their routine ( de Rus Jacquet et al, 2021 ). This localization of results might be related to distinct rates of contracting a SARS-CoV-2 infection and different socio-cultural characteristics among separate regions even in the same country.…”
Section: Sleep Impairmentmentioning
confidence: 99%